Nurses' competencies in primary health care: a Delphy technique study - Regina R Witt; Maria Cecília Puntel de Almeida; Vivian Elizabeth Araujo (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
An investigation on nurses´ primary health care practice was developed to identify and analyze nurses' general and specific competencies at the Brazilian Health System. This quantitative-qualitative research adopted the Delphi Technique as a method of study. Two groups of participants were selected. Fifty-two nurses and fifty-seven specialists accepted to participate in the study. Questionnaires were developed for data collection, including a Likert scale. A 75 percentage was adopted as a consensus criterion for scores 4 or 5 of this scale. Results showed 17 general and 8 specific competencies for the nursing group and 19 general and 9 specific competencies for the specialist group. These competencies were classified into ten areas of domain. This paper presents and discusses health care competencies found in this investigation.